Significances of the dialogic passage in the novel “Memory of the Body”by Ahlam Mosteghanemi(An interpretive approach of the opening dialogic passage of the third chapter of the novelfrom p. 77 to p. 88) (مجلة إحالات, 2026)
The article analyzes an extracted dialogue passage from the novel “Memory of the Body” by Ahlam Mostaganmi, located at the beginning of the third chapter of the novel and extending over elevenpages. The analysis is based on two principles: The first is the openness of the novel's text to multiplereadings due to its structural characteristic, and the second is the importance of the dialog and its writing methods in revealing the artistic value and symbolic depth of the novel. Our main objective was to highlight the significant value of the passage and the manifestations ofcreativity and transgression in it through three stages, starting from the structure of the dialog and itsconnotations, then its contents and the most important semantic dimensions inherent in it, up to the language of the dialog and its issues.